The Effects of Mineral Supplementation in Rapeseed Cake Diet on Thyroid Function and Meat Quality in Broiler Chickens - Tamás Tóth; Rita Éva Horváth; Ottó Dóka; Mihály Kovács; Hedvig Fébel (Agriculture)
Rapeseed is a high-quality protein source; however, its quality primarily depends on the variety, origin, and processing method. This study aimed to examine the effectiveness of a mineral supplement (“Peelko”; 27% Ca, 3.5% Mg, 800 mg/kg Fe) in terms of whether it is suitable for reducing the remaining antinutritional substances in cold-pressed rapeseed cake, thereby improving the nutrient content and digestibility of rapeseed. The experiment was carried out with 600 Ross-308 broilers divided into three feeding groups: the control diet contained extracted soybean meal, the R treatment included 10–15% cold-pressed rapeseed cake (in grower and finisher phases), and the R+ treatment consisted of the mineral supplement in addition to the cold-pressed rapeseed cake. R+ had a beneficial effect on the FCR in the grower and finisher feeding phases; moreover, it increased the weight of thyroid glands and the T3 and T4 hormone levels in the blood serum to a lesser extent than R when compared to C (p < 0.05). Diet-specific changes could be observed through the histological examination of thyroid glands, where the acini became larger when the unsupplemented cold-pressed rapeseed cake was fed (R group). Using the mineral supplement (R+ diet) decreased the acinus diameter compared to the R diet, with a similar value to that observed in control birds. The protein content in the breast and fat content in the thigh showed milder changes in R+ than R, compared to C (p < 0.05). The relative ratio of n-6 and n-3 fatty acids narrowed in both R and R+ meat samples compared to C (p < 0.05). R+ may have a more favorable effect on oxidation processes according to the better MDA values in fresh meat (p < 0.001) and samples after 1–2 months of storage (p < 0.05) than R when compared with C. The negative modifications in the color parameters (L*, a*, and b*) and the organoleptic properties of the meat were less significant with R+ than R, compared to the control (p < 0.05). According to the results of this study, the R+ treatment was able to reduce the antinutritional effects of rapeseed, as evident from the properties of the resulting animal products.